Capacitor Bank Voltage Equilibrium for MPPT in Single-Phase Single-Stage Five-Level Inverter for PV-Grid Application - Leonardus Heru Pratomo; F. Danang Wijaya; Eka Firmansyah (Indonesian Journal of Electrical Engineering and Computer Science, 2015)
Single-phase single-stage PV-Grid system using a five-level inverter has been investigated. Some of integration systems used two-stage converters, while others used single-stage converter. However, two-stage converters had a very complicated problem. The first converter acted as a maximum power point tracker to maximize power generated by sunlight energy to electric power, implemented by PV. The second stage was used as an interface to the grid. In single stage-converter was very simple in which an inverter was used for a maximum power point tracker and interface to the grid. This paper is designed to develop a single-stage PV-Grid system using a single-phase voltage source five-level inverter. The voltage equilibrium on capacitor was to make PV generate maximum power; hence, the equilibrium voltage between PV and five-level inverter output was proposed to deliver that maximum power generated by PV to the grid. Here, an analysis and a simulation were performed to demonstrate the design effectiveness. DOI: http://dx.doi.org/10.11591/telkomnika.v14i1.7646